Difah Resti Efrilia Pengaruh Layanan Konseling Kelompok dengan Teknik Desensitisasi Sistematik untuk Mengurangi Tingkat Kecemasan saat Menghadapi Ujian Siswa Kelas XI di SMA Negeri Keberbakatan Olahraga Bengkulu - Difah Resti Efrilia; Yessy Elita; Arsyadhani Mishbahuddin (UNIVERSITAS BENGKULU, 2023)
In this study the background of students' anxiety and to see the effect of group counseling using systematic desensitization techniques in reducing anxiety when facing exams for class XI students at the Bengkulu Sports Talent High School. This research is a type of experimental research one-group pretest-posttest design using quantitative methods. The subjects in this study were class XI students at the Bengkulu Sports Talent State Senior High School. Subjects were conducted using purposive sampling technique. How to obtain research data using a questionnaire (questionnaire) with a Likert scale. This study uses the T test data analysis technique (paired sample test). The results of the study prove that there is a significant effect of group counseling services with systematic desensitization techniques on reducing anxiety levels when facing student exams in class IX students. Keywords: Anxiety, Group Counseling, Systematic Desensitization Technique.